Estimated impact of COVID-19 on preventive care service delivery: an observational cohort study - Scott Laing; Sharon Johnston (BMC, 2021)
Abstract Background COVID-19 has caused significant healthcare service disruptions. Surgical backlogs have been estimated but not for other healthcare services. This study aims to estimate the backlog of preventive care services caused by COVID-19. Methods This observational study assessed preventive care screening rates at three primary care clinics in Ottawa, Ontario from March to November 2020 using data from 22,685 electronic medical records. The change in cervical cancer, colorectal cancer, and type 2 diabetes screening rates were crudely estimated using 2016 census data, estimating the volume of key services delayed by COVID-19 across Ontario and Canada. Results The mean percentage of patients appropriately screened for cervical cancer decreased by 7.5% (− 0.3% to − 14.7%; 95% CI), colorectal cancer decreased by 8.1% (− 0.3% to − 15.8%; 95% CI), and type 2 diabetes decreased by 4.5% (− 0.2% to − 8.7%; 95% CI). Crude estimates imply 288,000 cervical cancer (11,000 to 565,000; 95% CI), 326,000 colorectal cancer (13,000 to 638,000; 95% CI), and 274,000 type 2 diabetes screenings (13,000 to 535,000; 95% CI) may be overdue in Ontario. Nationally the deficits may be tripled these numbers. Re-opening measures have not reversed these trends. Interpretation COVID-19 decreased the delivery of preventive care services, which may cause delayed diagnoses, increased mortality, and increased health care costs. Virtual care and reopening measures have not restored the provision of preventive care services. Electronic medical record data could be leveraged to improve screening via panel management. Additional, system-wide primary care and laboratory capacity will be needed to restore pre-COVID-19 screening rates.